The law and economics of enhancing cartel enforcement: Using information from non-cartel investigations to prosecute cartels - Vivek Ghosal (Center for Economic Studies and ifo Institute (CESifo), 2011)
I present the following proposal: information revealed during non-cartel investigations by competition law enforcement authorities, such as evaluation of M&As or investigation of monopolization (dominance) conduct, should be directly used to investigate and prosecute cartels. Currently, in several jurisdictions, information acquired in, for example, a M&A investigation typically cannot be directly used for a cartel case due to the underlying statutes and the legal and administrative procedures that govern information use. Reviewing the management and corporate strategy literature, I note that M&As form a vital part of firms' core business strategy, with the longer-run strategic aspects being more important. These longer-run strategies could be jeopardized if the firms were engaging in collusion, as the likelihood of detection and prosecution would increase under the proposed rule change, which would punish bad (collusive) behavior. I argue that irrespective of exactly how many cartels are actually prosecuted via this channel, the proposal has the likelihood of creating a meaningful deterrence effect. I also discuss the potential downsides related to Type 1 errors and administrative costs. Overall, I argue that the proposed rule change could increase the efficiency and effectiveness of cartel enforcement, and open an additional front in the fight against hardcore cartels that operate within jurisdictions as well as internationally.
Keywords: A10; D49; K00; K14; K21; L00; L40; L44; L49; M00; 330; cartels; enforcement; law and economics; Kartellrecht; Rechtsdurchsetzung; Wettbewerbsaufsicht; Fusionskontrolle; Information; Spillover-Effekt; USA